Update on Management of Caustic and Foreign Body Ingestion in Children. (18th October 2009) - Betalli, Pietro; Rossi, Alfredo; Bini, Marta; Bacis, Giuseppe; Borrelli, Osvaldo; Cutrone, Cesare; Dall'Oglio, Luigi; d'Angelis, Gian Luigi; Falchetti, Diego; Farina, Maria Luisa; Gamba, PierGiorgio; Gandullia, Paolo; et al.
Abstract : The following recommendations for management of caustic and foreign body ingestion in children have been developed following a multicentre study performed by the Italian Society for Paediatric Gastroenterology, Hepatology and Nutrition (SIGENP) . They are principally addressed to medical professionals involved in casualty. Because there is paucity of good quality clinical trials in children on this topic, many of the recommendations are currently extrapolated from adult experiences or based on experts opinions. The document represents a level 2 to 5 degree of evidence (according to the Oxford Centre for Evidence-based Medicine Levels of Evidence), gathered from clinical experience, recent studies, and expert reports discussed during a consensus conference of the Endoscopic Section of the Italian Society of Paediatric Gastroenterology Hepatology and Nutrition. This working group comprises paediatricians, endoscopists, paediatric surgeons, toxicologists, and ENT surgeons, who are all actively involved in the management of these children. Recommendations are intended to serve as an aid to clinical judgement, not to replace it and therefore do not provide answers to every clinical question; nor does adherence to them ensure a successful outcome in every case. The ultimate decision on the clinical management of an individual patient will always depend on the specific clinical circumstances of the patient, and on the clinical judgement of the health care team.